(untitled) (Current Problems in Rail Vehicles, 2025)
The safety of rail transport is also affected by the braking capabilities of the vehicles. In the case of vehicles with disc brakes, there is no cleaning of the wheel surface during braking, which, combined with an increase in the coefficient of friction during braking, increases the probability of wheelset sliding, damage to the wheel surface and an increase in braking distance. The paper deals with selected problems of braking of freight wagons with disc brakes, which are currently being solved at the Faculty of Transport Engineering of the University of Pardubice as part of students’ final theses. The theses were focused on the determination of the coefficient of friction between the disc and the brake pads in the conditions of the company DAKO-CZ, a.s., and on design of a simple device for the protection of the running surface of the wheels during braking of freight wagons by disc brakes.